The ATLAS pixel sensor - Klaiber-Lodewigs, Jonas M. (Technische Universität Dortmund, 2006)
The planning, construction and commissioning of multi-purpose physics detectors for the LHC proton-proton collider at CERN poses new challenges to the involved institutes regarding scientific, technological and organizational aspects of the process. In the case of the central vertex tracking systems, very complex assemblies have to be produced in large numbers and integrated into a device reliable enough to function for a planned experimental lifetime of at least ten years and in a radiation environment up to doses of several hundred kGy and fluences well above 1014 1MeV neutron equivalents/cm2 for the innermost parts of the tracking system. A quality assurance plan has to be implemented to ensure high quality of all parts according to the necessary performance parameters, define technical specifications accordingly and provide a good understanding of particle-detector interaction and the physical properties of the detector to extrapolate detector behaviour during the experiment. This thesis gives a detailed overview of the motivation, physics and organizational aspects and results of the quality assurance program for the silicon sensor used in the pixel subdetector for the ATLAS multi-purpose experiment. The sensor design used is shown to be well suitable for assembly and long term operation within the ATLAS experiment, and the quality plan implemented for sensor production has proven highly indicative for monitoring crucial aspects of sensor quality. In addition, problems within sensor production could be pinpointed at an early stage and further insights into the physical properties of sensors and parameters of their operation could be gained.
properties, characterization and quality control
Keywords: ATLAS; Vertexdetektor; Vertex detector; Pixel; Sensor; Pixelsensor; Qualitätssicherung; Quality assurance; Quality control; 530